On the solution of the steady‐state diffusion problem for ferromagnetic particles in a magnetic fluid - Polevikov, Viktor; Tobiska, Lutz (Mathematical Modelling and Analysis, 2008)
A mathematical model for the diffusion process of ferromagnetic particles in a magnetic fluid is described. The unique solvability of the steady‐state particle concentration problem is investigated and an analytical expression for its solution is found. In case that the fluid is under the action of a high‐gradient magnetic field a Stefan‐type diffusion problem can arise. An algorithm for solving the Stefan‐type steady‐state problem is developed. First Published Online: 14 Oct 2010